Ultrasonographic assessment of liver and spleen in Jamunapari goats - Raj, Nitin; Kumar, Gulshan; Pandey, R.P. (Indian Journal of Veterinary Surgery, 2025)
Twenty normal, healthy, adult Jamunapari goats were subjected to ultrasonographic imaging of the liver and spleen along with their associated structure and vasculature. Doppler ultrasonography of the portal vein and caudal vena cava was also done. The liver was visible in the 7th through 12th intercostal space (ICS) on the right thorax. The parenchyma was homogenously echogenic. The measurements of the distance of dorsal visible margin (DVM) and the ventral visible margin (VVM) of liver from the dorsal mid-line were recorded. The mean±SE value of visible size of liver was greatest at 9th ICS (11.23±0.12 cm) and smallest at 12th ICS (7.50±0.11 cm). The thickness of liver was greatest (5.76±0.11 cm) at 11th ICS and least (4.79±0.04 cm) at 12th ICS. The gallbladder was visible through 10th ICS on the right side of thorax and appeared in various shapes such as spherical, oval, or pear-shaped. The portal vein appeared as an anechoic structure, having hyperechoic wall. The caudal vena cava (CVC) appeared as a triangular anechoic structure, deeper and medial to portal vein. The mean±SE value of circumference of the CVC was 5.45±0.16 cm. The mean velocity in the CVC and the portal vein were 25.92±2.7 cm/s and 34.15±4.4 cm/s, respectively. The spleen was visible from 9th through 12th ICS in the left side of thorax, running caudo-dorsally to cranioventrally with a uniformly echogenic parenchyma. The distance of the DVM of spleen from the dorsal midline was largest in 9th ICS (11.93±0.36 cm) and smallest in 12th ICS (6.26±0.23 cm). The distance of VVM of spleen from the dorsal midline was largest in 9th ICS (17.66±0.03 cm) and smallest in 12th ICS (5.17±0.15 cm). The size of spleen was greatest in 10th ICS (7.26±0.09 cm) and least in 12th ICS (5.17±0.15 cm). These sonographic measurements of liver, gall bladder, portal vein, caudal vena cava, and spleen may serve as reference values and be helpful in faster detection of many hepatic and splenic ailments.